PREFERENSI PEMILIK USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP TENAGA KERJA YANG DIBUTUHKAN USAHANYA (STUDI PADA PEMILIK UMKM DI KOTA MALANG TAHUN 2017) - Gantara, Rivelino Brian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Indonesia is a country with the third largest population in the world. With such a large population, the government is required to create jobs in order to accommodate the number of labor force that exists. In the era of intense business competition especially in urban areas has become an obstacle for job seekers, due to the increasingly tight competition between people who are looking for experience to the already experienced. Not only on the experience that the competition of the labor but there are some things such as education and skills. In this case the business owner or UMKM in Malang also participate in reducing the number of manpower that is by having preference in the selection of labor needed later, the preference required by the owner of UMKM include education level, work experience, behavior (habit) and gender . This study aims to determine the preferences of MSME owners to Gender, Smoking and Smoking Habits, Education Level, Work Experience in the selection of workers needed in the city of Malang. The approach used is quantitative explanatory research approach with survey research method. The type of data used is primary data and secondary data. The result obtained is the owner of umkm in Malang City to pay attention to preference (gender, behavior, education level, work experience) in choosing the labor needed for the business because the four criteria can affect a production and profit which will be obtained by the owner of UMKM.Keywords: Preferences of MSME owners, labor